Electrophoretic Detection of Single-Nucleotide Polymorphisms. (April 2000) - See, Deven; Kanazin, Vladimir; Talbert, Hope; Blake, Tom
Single-nucleotide polymorphisms (SNPs) represent the most prevalent class of genetic markers available for linkage disequilibrium or cladistic analyses. PCR primers may be labeled with fluorescent dyes and used to rapidly and accurately differentiate among alleles that are defined by a single-nucleotide differences. Here, we describe the primer-mediated detection of SNPs based on primer mismatch during allele-specific amplification of preamplified target sequences. Primers are labeled with different fluors at their 5′ nucleotides, with their 3′ termini at the transition mutation that defines allelic variation at the target locus. Each primer perfectly matches one of the two available alleles for each locus. Electrophoretic detection permits characterization of the product both by size and fluor. This report demonstrates some of the capabilities of this assay, including heterozygote determination and multiplexed analysis.